Menguatkan Peran Ibu dalam Mencetak Generasi Emas: Program Pemberdayaan di DPC IWAPI Depok - S Syah; ND Natashia; M Handini; Erni Handayani (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
The community service project titled "Strengthening the Role of Mothers in Shaping the Golden Generation: Empowerment Program at DPC IWAPI Depok" aims to empower mothers through entrepreneurship training, business management, and leadership, in order to enhance their capacity to manage businesses and play an active role in community economic development. This program involves 50 mothers who are members of DPC IWAPI Depok, who actively participated in the planning and implementation processes. The results of the program indicate an improvement in entrepreneurship and leadership skills among the mothers, as well as the emergence of local leaders capable of organizing community economic activities. Additionally, significant social changes occurred, including the formation of women-based business groups that support each other in developing their businesses. This empowerment has led to the creation of new social structures and behavioral changes that support women's empowerment at large. These findings align with theories of empowerment, social change, and transformational leadership, which emphasize the importance of individual roles in influencing social change.